A kind of anti-pollution ultrafiltration membrane and preparation method thereof
Patent Information
- Application Number
- CN202410604127.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-15
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-05-15
AI Technical Summary
然而,上述超滤膜亲水性仍然不足,使得其抗污染性能仍然有待进一步提高
[0029] (1) The preparation method of anti-pollution ultrafiltration membrane disclosed in the present invention can be realized by using conventional equipment and operations, with less capital investment, low energy consumption, high preparation efficiency and finished product qualification rate, suitable for industrial production, and has a higher Promote application value.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic polymer materials, and in particular to an anti-pollution ultrafiltration membrane and a preparation method thereof. Background Art
[0002] Ultrafiltration membrane is a microporous filtration membrane between nanofiltration membrane and microfiltration membrane. It mainly separates proteins, enzymes, nucleic acids, polysaccharides, peptides, antibiotics, and viruses. Since there is no phase transfer during use and no toxic or harmful chemicals need to be added, it is widely used in sewage treatment, seawater desalination, food processing, biomedicine, bioengineering, chemical industry and other fields.
[0003] During the use of ultrafiltration membranes, the deposition or adsorption of various pollutants will cause a serious decrease in membrane flux, requiring frequent cleaning, which can easily reduce the service life of ultrafiltration system membrane elements and increase the operating cost of the system, thereby limiting the wider application of ultrafiltration membranes. Therefore, improving the anti-pollution ability of ultrafiltration membranes is one of the problems that the existing technology urgently needs to solve.
[0004] At present, the main materials of ultrafiltration membranes are PVDF, PES, PS, PVC, PAN, PP, etc. Among the many materials, PES (polyethersulfone) has excellent chemical properties, thermal stability and high mechanical strength. The use of PES ultrafiltration membranes to separate organic pollutants is not only efficient and low-cost, but also has no secondary pollutants, and is environmentally friendly and reliable. However, polyethersulfone ultrafiltration membranes are highly hydrophobic and have poor pollution resistance. They are prone to form a mud cake layer on the membrane surface, blocking the membrane pores, forming a very poor solubility, and causing a serious decrease in membrane flux, which greatly hinders the application of polyethersulfone ultrafiltration membranes in the field of actual membrane separation.
[0005] In order to solve the above problems, the Chinese invention patent with the authorization announcement number CN110449036B discloses a method for preparing an anti-pollution ultrafiltration membrane. By adding modified nano-lanthanum oxide and modified nano-cerium oxide to the membrane-forming material, the modified nano-lanthanum oxide and modified nano-cerium oxide have a large specific surface area, which can improve the performance of the ultrafiltration membrane. Lanthanum oxide and cerium oxide are both rare earth oxides. Applying them to the ultrafiltration membrane can greatly improve the pure water flux of the ultrafiltration membrane and the flux recovery rate is high. Experiments show that the ultrafiltration membrane prepared by adding modified nano-lanthanum oxide and modified nano-cerium oxide has a pure water flux of up to 170L / m 2·h or more, and the flux recovery rate can reach more than 90%, and the anti-pollution ability is greatly improved; the invention adds modified nano-lanthanum oxide and modified nano-cerium oxide, and there is a synergistic effect between the two oxides. Compared with the ultrafiltration membrane prepared by adding only nano-lanthanum oxide or nano-cerium oxide, its pure water flux is greatly improved. However, the hydrophilicity of the above ultrafiltration membrane is still insufficient, so that its anti-pollution performance still needs to be further improved. And the use of nano rare earth oxides greatly increases its preparation cost, so that its cost performance needs to be further improved.
[0006] Therefore, the development of an anti-pollution ultrafiltration membrane with good anti-pollution performance, sufficient pure water flux, and high BSA retention rate and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the ultrafiltration membrane field. Summary of the invention
[0007] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide an anti-pollution ultrafiltration membrane with good anti-pollution performance, sufficient pure water flux and high BSA retention rate and a preparation method thereof.
[0008] To achieve the above purpose, the technical scheme adopted by the present invention is: an anti-pollution ultrafiltration membrane, comprising the following raw materials in parts by weight: 80 parts of hydrophilic modified polyether sulfone, 2-4 parts of coupling agent, 3-5 parts of Al-Nb-Sc-O-Te, 15-25 parts of additives, 5-8 parts of polyethylene glycol diacrylate, 2-4 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 3-5 parts of 1-allyl-3-vinyl imidazole chloride; the hydrophilic modified polyether sulfone is trishydroxymethylaminomethanesulfonic acid modified polyether sulfone.
[0009] Preferably, the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.
[0010] Preferably, the additive is any one of polyvinyl pyrrolidone K-30, polyvinyl pyrrolidone K-17, polyvinyl pyrrolidone K-60, polyethylene glycol 200, and polyethylene glycol 400.
[0011] Preferably, the number average molecular weight of the polyethylene glycol diacrylate is 400.
[0012] Preferably, the preparation method of the hydrophilic modified polyether sulfone comprises the following steps: adding polyether sulfone, polyphosphoric acid, phosphorus pentoxide and tris(hydroxymethyl)aminomethanesulfonic acid into a reaction kettle equipped with a reflux device and containing dimethyl sulfoxide, stirring and reacting at 175-183° C. for 6-10 hours, then removing the solvent by rotary evaporation, washing the product with water for 3-6 times, and finally drying it in a vacuum drying oven at 90-100° C. to constant weight to obtain the hydrophilic modified polyether sulfone.
[0013] Preferably, the mass ratio of the polyether sulfone, polyphosphoric acid, phosphorus pentoxide, tris(hydroxymethyl)aminomethanesulfonic acid) and dimethyl sulfoxide is 3:(0.1-0.3):(0.3-0.5):(0.5-1):(10-16).
[0014] Preferably, the polyethersulfone is provided by Solvay with a grade of 3000MP polyethersulfone.
[0015] Preferably, the preparation method of Al-Nb-Sc-O-Te comprises the following steps: dispersing an aluminum source, a niobium source, a scandium source and a tellurium source in an alcohol solvent, stirring evenly, slowly adding sodium acetate, and vigorously stirring for 2 hours, transferring the mixture to a polytetrafluoroethylene-lined hydrothermal reactor, and reacting at 190-222°C for 12-24 hours; after cooling, repeatedly washing with anhydrous ethanol, drying to constant weight in a vacuum drying oven at 80-90°C, grinding through a 400-800 mesh sieve, and then calcining at 600-800°C for 5-8 hours.
[0016] Preferably, the mass ratio of the aluminum source, niobium source, scandium source, tellurium source, alcohol solvent and sodium acetate is 1:(0.05-0.1):(0.01-0.03):0.003:(10-20):3.
[0017] Preferably, the aluminum source is at least one of aluminum chloride and aluminum nitrate; the niobium source is at least one of niobium chloride and niobium nitrate; the scandium source is scandium nitrate; and the tellurium source is sodium tellurate.
[0018] Preferably, the alcohol solvent is at least one of ethanol, ethylene glycol and n-butanol.
[0019] Another object of the present invention is to provide a method for preparing the anti-pollution ultrafiltration membrane, comprising the following steps:
[0020] Step S1, mixing a hydrophilic modified polyethersulfone, a coupling agent, Al-Nb-Sc-O-Te and an additive to obtain a mixture, adding the mixture into an organic solvent, heating and stirring for 4-6 hours, and preparing a casting solution;
[0021] Step S2, the casting solution prepared in step S1 is placed in a static state for degassing, and then the film is scraped, and then placed in a deionized water coagulation bath at 65-75° C., and after the film is formed, it is washed with deionized water and dried naturally to obtain a primary film;
[0022] Step S3, polyethylene glycol diacrylate, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt and 1-allyl-3-vinyl imidazole chloride are added into water in sequence, and dispersed evenly to obtain a dispersion; then the primary membrane is immersed in the dispersion, and heated under a nitrogen atmosphere by using 60 The membrane is irradiated by a Co-γ ray source, and then washed and dried to obtain an anti-pollution ultrafiltration membrane.
[0023] Preferably, the mass ratio of the mixed material to the organic solvent in step S1 is 1:(6-10).
[0024] Preferably, the organic solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.
[0025] Preferably, the temperature of the heating and stirring in step S1 is 60-80°C.
[0026] Preferably, in step S3, the mass ratio of polyethylene glycol diacrylate to water is 1:(5-8).
[0027] Preferably, the irradiation in step S3 is carried out at room temperature, the irradiation dose rate is 10 to 430 Gy / min, and the irradiation dose is 10 to 70 kGy.
[0028] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0029] (1) The method for preparing the anti-pollution ultrafiltration membrane disclosed in the present invention can be realized by using conventional equipment and operations, with low capital investment, low energy consumption, high preparation efficiency and finished product qualification rate, suitable for industrial production, and high promotion and application value.
[0030] (2) The anti-pollution ultrafiltration membrane disclosed in the present invention is made of the following raw materials in parts by weight: 80 parts of hydrophilic modified polyethersulfone, 2-4 parts of coupling agent, 3-5 parts of Al-Nb-Sc-O-Te, 15-25 parts of additives, 5-8 parts of polyethylene glycol diacrylate, 2-4 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 3-5 parts of 1-allyl-3-vinyl imidazole chloride; the hydrophilic modified polyethersulfone is tris(hydroxymethyl)aminomethanesulfonic acid modified polyethersulfone. Through the reasonable selection of raw material types and dosage ratios, the mutual coordination and joint action of the raw materials, the prepared ultrafiltration membrane has good anti-pollution performance, sufficient pure water flux, and high BSA retention rate.
[0031] (3) The anti-pollution ultrafiltration membrane disclosed in the present invention can improve the anti-pollution performance, pure water flux and BSA retention rate by adding Al-Nb-Sc-O-Te. Polyethersulfone is modified by hydrophilicity and more hydrophilic groups are introduced into the molecular structure, which can improve the compatibility between polyethersulfone and other raw materials, thereby improving the performance stability; at the same time, its hydrophilicity can be improved, thereby improving the anti-pollution performance of the ultrafiltration membrane. Polyethylene glycol diacrylate, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt and 1-allyl-3-vinyl imidazole chloride can be radiation-grafted to the membrane surface by irradiation to form a hydrophilic cross-linked interpenetrating network structure, which can further improve the anti-pollution performance, pure water flux and BSA retention rate; and the ester group, amphoteric organic ion salt structure and imidazole salt structure introduced at the same time can cooperate with each other to further improve the above-mentioned performance. DETAILED DESCRIPTION
[0032] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0033] Example 1
[0034] An anti-pollution ultrafiltration membrane is made of the following raw materials in parts by weight: 80 parts of hydrophilic modified polyethersulfone, 2 parts of coupling agent, 3 parts of Al-Nb-Sc-O-Te, 15 parts of additives, 5 parts of polyethylene glycol diacrylate, 2 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 3 parts of 1-allyl-3-vinyl imidazole chloride; the hydrophilic modified polyethersulfone is tris(hydroxymethylaminomethanesulfonic acid) modified polyethersulfone.
[0035] The coupling agent is silane coupling agent KH550; the additive is polyvinyl pyrrolidone K-30; and the number average molecular weight of the polyethylene glycol diacrylate is 400.
[0036] The preparation method of the hydrophilic modified polyethersulfone comprises the following steps: adding polyethersulfone, polyphosphoric acid, phosphorus pentoxide and tris(hydroxymethyl)aminomethanesulfonic acid) into a reaction kettle with a reflux device and containing dimethyl sulfoxide, stirring and reacting at 175°C for 6 hours, then removing the solvent by rotary evaporation, washing the product with water for 3 times, and finally drying the product in a vacuum drying oven at 90°C to constant weight to obtain the hydrophilic modified polyethersulfone; the mass ratio of the polyethersulfone, polyphosphoric acid, phosphorus pentoxide, tris(hydroxymethyl)aminomethanesulfonic acid and dimethyl sulfoxide is 3:0.1:0.3:0.5:10; the polyethersulfone is provided by Solvay with a grade of 3000MP polyethersulfone; through weight change analysis, the grafting rate is 12.9%, calculated as follows: grafting rate = (polyethersulfone dry weight after modification - polyethersulfone dry weight before modification) / polyethersulfone dry weight before modification × 100%.
[0037] The preparation method of Al-Nb-Sc-O-Te comprises the following steps: dispersing an aluminum source, a niobium source, a scandium source and a tellurium source in an alcohol solvent, stirring evenly, slowly adding sodium acetate, stirring vigorously for 2 hours, transferring the mixture to a hydrothermal reactor lined with polytetrafluoroethylene, and reacting at 190°C for 12 hours; cooling and repeatedly washing with anhydrous ethanol, drying to constant weight in a vacuum drying oven at 80°C, grinding through a 400-mesh sieve, and calcining at 600°C for 5 hours; the mass ratio of the aluminum source, niobium source, scandium source, tellurium source, alcohol solvent and sodium acetate is 1:0.05:0.01:0.003:10:3; the aluminum source is aluminum chloride; the niobium source is niobium chloride; the scandium source is scandium nitrate; the tellurium source is sodium tellurate; and the alcohol solvent is ethanol.
[0038] Another object of the present invention is to provide a method for preparing the anti-pollution ultrafiltration membrane, comprising the following steps:
[0039] Step S1, mixing a hydrophilic modified polyethersulfone, a coupling agent, Al-Nb-Sc-O-Te and an additive to obtain a mixture, adding the mixture into an organic solvent, heating and stirring for 4 hours to prepare a casting solution;
[0040] Step S2, the casting solution prepared in step S1 is placed in a static state for degassing, and then the film is scraped, and then placed in a deionized water coagulation bath at 65° C. After the film is formed, it is washed with deionized water and dried naturally to obtain a primary film;
[0041] Step S3, polyethylene glycol diacrylate, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt and 1-allyl-3-vinyl imidazole chloride are added into water in sequence, and dispersed evenly to obtain a dispersion; then the primary membrane is immersed in the dispersion, and heated under a nitrogen atmosphere by using 60The membrane was irradiated with a Co-γ ray source, and then washed and dried in sequence to obtain an anti-pollution ultrafiltration membrane. The weight change of the membrane before and after the step was calculated, and the grafting rate of the membrane through this step was 9.5%, and the calculation formula was as follows: grafting rate = (anti-pollution ultrafiltration membrane dry weight-initial membrane dry weight) / initial membrane dry weight × 100%; through elemental analysis and weight change calculation, the mass ratio of the structural units introduced on the membrane surface by polyethylene glycol diacrylate, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 1-allyl-3-vinylimidazolium chloride was 4.97:1.99:2.98.
[0042] The mass ratio of the mixed material and the organic solvent in step S1 is 1:6; the organic solvent is dimethyl sulfoxide; the temperature of heating and stirring in step S1 is 60°C; the mass ratio of polyethylene glycol diacrylate and water in step S3 is 1:5; the irradiation in step S3 is carried out at room temperature, the irradiation dose rate is 10Gy / min, and the irradiation dose is 10kGy.
[0043] Example 2
[0044] An anti-pollution ultrafiltration membrane is made of the following raw materials in parts by weight: 80 parts of hydrophilic modified polyethersulfone, 2.5 parts of coupling agent, 3.5 parts of Al-Nb-Sc-O-Te, 17 parts of additives, 6 parts of polyethylene glycol diacrylate, 2.5 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 3.5 parts of 1-allyl-3-vinyl imidazole chloride; the hydrophilic modified polyethersulfone is tris(hydroxymethylaminomethanesulfonic acid) modified polyethersulfone.
[0045] The coupling agent is silane coupling agent KH560; the additive is polyvinyl pyrrolidone K-17; and the number average molecular weight of the polyethylene glycol diacrylate is 400.
[0046] The preparation method of the hydrophilic modified polyethersulfone comprises the following steps: adding polyethersulfone, polyphosphoric acid, phosphorus pentoxide and tris(hydroxymethyl)aminomethanesulfonic acid) into a reaction kettle with a reflux device and containing dimethyl sulfoxide, stirring and reacting at 178°C for 7h, then removing the solvent by rotary evaporation, washing the product with water for 4 times, and finally drying the product in a vacuum drying oven at 93°C to constant weight to obtain the hydrophilic modified polyethersulfone; the mass ratio of the polyethersulfone, polyphosphoric acid, phosphorus pentoxide, tris(hydroxymethyl)aminomethanesulfonic acid and dimethyl sulfoxide is 3:0.15:0.35:0.6:12; the polyethersulfone is provided by Solvay with a grade of 3000MP polyethersulfone.
[0047] The preparation method of Al-Nb-Sc-O-Te comprises the following steps: dispersing an aluminum source, a niobium source, a scandium source and a tellurium source in an alcohol solvent, stirring evenly, slowly adding sodium acetate, stirring vigorously for 2 hours, transferring the mixture to a hydrothermal reactor lined with polytetrafluoroethylene, and reacting at 200°C for 16 hours; cooling and repeatedly washing with anhydrous ethanol, drying to constant weight in a vacuum drying oven at 83°C, grinding through a 500-mesh sieve, and calcining at 650°C for 6 hours; the mass ratio of the aluminum source, niobium source, scandium source, tellurium source, alcohol solvent and sodium acetate is 1:0.06:0.015:0.003:13:3; the aluminum source is aluminum nitrate; the niobium source is niobium nitrate; the scandium source is scandium nitrate; the tellurium source is sodium tellurate; and the alcohol solvent is ethylene glycol.
[0048] A method for preparing the anti-pollution ultrafiltration membrane comprises the following steps:
[0049] Step S1, mixing a hydrophilic modified polyethersulfone, a coupling agent, Al-Nb-Sc-O-Te and an additive to obtain a mixture, adding the mixture into an organic solvent, heating and stirring for 4.5 hours, and preparing a casting solution;
[0050] Step S2, the casting solution prepared in step S1 is placed in a static state for degassing, and then the film is scraped, and then placed in a deionized water coagulation bath at 68° C. After the film is formed, it is washed with deionized water and dried naturally to obtain a primary film;
[0051] Step S3, polyethylene glycol diacrylate, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt and 1-allyl-3-vinyl imidazole chloride are added into water in sequence, and dispersed evenly to obtain a dispersion; then the primary membrane is immersed in the dispersion, and heated under a nitrogen atmosphere by using 60 The membrane is irradiated by a Co-γ ray source, and then washed and dried to obtain an anti-pollution ultrafiltration membrane.
[0052] The mass ratio of the mixed material and the organic solvent in step S1 is 1:7; the organic solvent is N,N-dimethylformamide; the temperature of heating and stirring in step S1 is 65°C; the mass ratio of polyethylene glycol diacrylate and water in step S3 is 1:6; the irradiation in step S3 is carried out at room temperature, the irradiation dose rate is 130Gy / min, and the irradiation dose is 35kGy.
[0053] Example 3
[0054] An anti-pollution ultrafiltration membrane is made of the following raw materials in parts by weight: 80 parts of hydrophilic modified polyethersulfone, 3 parts of coupling agent, 4 parts of Al-Nb-Sc-O-Te, 20 parts of additives, 6.5 parts of polyethylene glycol diacrylate, 3 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 4 parts of 1-allyl-3-vinyl imidazole chloride; the hydrophilic modified polyethersulfone is tris(hydroxymethylaminomethanesulfonic acid) modified polyethersulfone.
[0055] The coupling agent is silane coupling agent KH570; the additive is polyvinyl pyrrolidone K-60; and the number average molecular weight of the polyethylene glycol diacrylate is 400.
[0056] The preparation method of the hydrophilic modified polyethersulfone comprises the following steps: adding polyethersulfone, polyphosphoric acid, phosphorus pentoxide and tris(hydroxymethyl)aminomethanesulfonic acid into a reaction kettle with a reflux device and containing dimethyl sulfoxide, stirring and reacting at 179°C for 8 hours, then removing the solvent by rotary evaporation, washing the product with water for 5 times, and finally drying the product in a vacuum drying oven at 95°C to constant weight to obtain the hydrophilic modified polyethersulfone; the mass ratio of the polyethersulfone, polyphosphoric acid, phosphorus pentoxide, tris(hydroxymethyl)aminomethanesulfonic acid and dimethyl sulfoxide is 3:0.2:0.4:0.75:13; the polyethersulfone is provided by Solvay with a grade of 3000MP polyethersulfone.
[0057] The preparation method of Al-Nb-Sc-O-Te comprises the following steps: dispersing an aluminum source, a niobium source, a scandium source and a tellurium source in an alcohol solvent, stirring evenly, slowly adding sodium acetate, stirring vigorously for 2 hours, transferring the mixture to a hydrothermal reactor lined with polytetrafluoroethylene, and reacting at 212°C for 19 hours; cooling and repeatedly washing with anhydrous ethanol, drying to constant weight in a vacuum drying oven at 85°C, grinding through a 600-mesh sieve, and calcining at 700°C for 6.5 hours; the mass ratio of the aluminum source, niobium source, scandium source, tellurium source, alcohol solvent and sodium acetate is 1:0.08:0.02:0.003:15:3; the aluminum source is aluminum chloride; the niobium source is niobium nitrate; the scandium source is scandium nitrate; the tellurium source is sodium tellurate; and the alcohol solvent is n-butanol.
[0058] A method for preparing the anti-pollution ultrafiltration membrane comprises the following steps:
[0059] Step S1, mixing a hydrophilic modified polyethersulfone, a coupling agent, Al-Nb-Sc-O-Te and an additive to obtain a mixture, adding the mixture into an organic solvent, heating and stirring for 5 hours, and preparing a casting solution;
[0060] Step S2, the casting solution prepared in step S1 is placed in a static state for degassing, and then the film is scraped, and then placed in a deionized water coagulation bath at 70° C. After the film is formed, it is washed with deionized water and dried naturally to obtain a primary film;
[0061] Step S3, polyethylene glycol diacrylate, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt and 1-allyl-3-vinyl imidazole chloride are added into water in sequence, and dispersed evenly to obtain a dispersion; then the primary membrane is immersed in the dispersion, and heated under a nitrogen atmosphere by using 60 The membrane is irradiated by a Co-γ ray source, and then washed and dried to obtain an anti-pollution ultrafiltration membrane.
[0062] The mass ratio of the mixed material and the organic solvent in step S1 is 1:8; the organic solvent is N,N-dimethylacetamide; the temperature of heating and stirring in step S1 is 70°C; the mass ratio of polyethylene glycol diacrylate and water in step S3 is 1:6.5; the irradiation in step S3 is carried out at room temperature, the irradiation dose rate is 260Gy / min, and the irradiation dose is 40kGy.
[0063] Example 4
[0064] An anti-pollution ultrafiltration membrane is made of the following raw materials in parts by weight: 80 parts of hydrophilic modified polyethersulfone, 3.5 parts of coupling agent, 4.5 parts of Al-Nb-Sc-O-Te, 23 parts of additives, 7.5 parts of polyethylene glycol diacrylate, 3.5 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 4.5 parts of 1-allyl-3-vinyl imidazole chloride; the hydrophilic modified polyethersulfone is tris(hydroxymethylaminomethanesulfonic acid) modified polyethersulfone.
[0065] The coupling agent is a mixture of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570 in a mass ratio of 1:2:3; the additive is a mixture of polyvinyl pyrrolidone K-30, polyvinyl pyrrolidone K-17, polyvinyl pyrrolidone K-60, polyethylene glycol 200, and polyethylene glycol 400 in a mass ratio of 1:1:3:2:4; the number average molecular weight of the polyethylene glycol diacrylate is 400.
[0066] The preparation method of the hydrophilic modified polyethersulfone comprises the following steps: adding polyethersulfone, polyphosphoric acid, phosphorus pentoxide and tris(hydroxymethyl)aminomethanesulfonic acid into a reaction kettle with a reflux device and containing dimethyl sulfoxide, stirring and reacting at 181°C for 9.5 hours, then removing the solvent by rotary evaporation, washing the product with water for 6 times, and finally drying the product in a vacuum drying oven at 98°C to constant weight to obtain the hydrophilic modified polyethersulfone; the mass ratio of the polyethersulfone, polyphosphoric acid, phosphorus pentoxide, tris(hydroxymethyl)aminomethanesulfonic acid and dimethyl sulfoxide is 3:0.25:0.45:0.9:15; the polyethersulfone is provided by Solvay with a grade of 3000MP polyethersulfone.
[0067] The preparation method of Al-Nb-Sc-O-Te comprises the following steps: dispersing an aluminum source, a niobium source, a scandium source and a tellurium source in an alcohol solvent, stirring evenly, slowly adding sodium acetate, and vigorously stirring for 2 hours, transferring the mixture to a hydrothermal reactor lined with polytetrafluoroethylene, and reacting at 218° C. for 22 hours; cooling and repeatedly washing with anhydrous ethanol, drying to constant weight in a vacuum drying oven at 88° C., grinding through a 750-mesh sieve, and calcining at 780° C. for 7.5 hours; The mass ratio of the aluminum source, niobium source, scandium source, tellurium source, alcohol solvent and sodium acetate is 1:0.09:0.025:0.003:18:3; the aluminum source is a mixture of aluminum chloride and aluminum nitrate in a mass ratio of 3:5; the niobium source is a mixture of niobium chloride and niobium nitrate in a mass ratio of 1:3; the scandium source is scandium nitrate; the tellurium source is sodium tellurite; the alcohol solvent is a mixture of ethanol, ethylene glycol and n-butanol in a mass ratio of 1:2:1.
[0068] A method for preparing the anti-pollution ultrafiltration membrane comprises the following steps:
[0069] Step S1, mixing a hydrophilic modified polyethersulfone, a coupling agent, Al-Nb-Sc-O-Te and an additive to obtain a mixture, adding the mixture into an organic solvent, heating and stirring for 5.5 hours, and preparing a casting solution;
[0070] Step S2, the casting solution prepared in step S1 is placed in a static state for degassing, and then the film is scraped, and then placed in a deionized water coagulation bath at 73° C. After the film is formed, it is washed with deionized water and dried naturally to obtain a primary film;
[0071] Step S3, polyethylene glycol diacrylate, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt and 1-allyl-3-vinyl imidazole chloride are added into water in sequence, and dispersed evenly to obtain a dispersion; then the primary membrane is immersed in the dispersion, and heated under a nitrogen atmosphere by using 60The membrane is irradiated by a Co-γ ray source, and then washed and dried to obtain an anti-pollution ultrafiltration membrane.
[0072] The mass ratio of the mixed material and the organic solvent in step S1 is 1:9.5; the organic solvent is dimethyl sulfoxide; the temperature of heating and stirring in step S1 is 78°C; the mass ratio of polyethylene glycol diacrylate and water in step S3 is 1:7.5; the irradiation in step S3 is carried out at room temperature, the irradiation dose rate is 400Gy / min, and the irradiation dose is 50kGy.
[0073] Example 5
[0074] An anti-pollution ultrafiltration membrane is made of the following raw materials in parts by weight: 80 parts of hydrophilic modified polyethersulfone, 4 parts of coupling agent, 5 parts of Al-Nb-Sc-O-Te, 25 parts of additives, 8 parts of polyethylene glycol diacrylate, 4 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 5 parts of 1-allyl-3-vinyl imidazole chloride; the hydrophilic modified polyethersulfone is tris(hydroxymethylaminomethanesulfonic acid) modified polyethersulfone.
[0075] The coupling agent is silane coupling agent KH550; the additive is polyethylene glycol 400; and the number average molecular weight of the polyethylene glycol diacrylate is 400.
[0076] The preparation method of the hydrophilic modified polyethersulfone comprises the following steps: adding polyethersulfone, polyphosphoric acid, phosphorus pentoxide and tris(hydroxymethyl)aminomethanesulfonic acid into a reaction kettle with a reflux device and containing dimethyl sulfoxide, stirring and reacting at 183°C for 10 hours, then removing the solvent by rotary evaporation, washing the product with water for 6 times, and finally drying it in a vacuum drying oven at 100°C to constant weight to obtain the hydrophilic modified polyethersulfone; the mass ratio of the polyethersulfone, polyphosphoric acid, phosphorus pentoxide, tris(hydroxymethyl)aminomethanesulfonic acid and dimethyl sulfoxide is 3:0.3:0.5:1:16; the polyethersulfone is provided by Solvay with a grade of 3000MP polyethersulfone.
[0077] The preparation method of Al-Nb-Sc-O-Te comprises the following steps: dispersing an aluminum source, a niobium source, a scandium source and a tellurium source in an alcohol solvent, stirring evenly, slowly adding sodium acetate, stirring vigorously for 2 hours, transferring the mixture to a hydrothermal reactor lined with polytetrafluoroethylene, and reacting at 222°C for 24 hours; cooling and repeatedly washing with anhydrous ethanol, drying to constant weight in a vacuum drying oven at 90°C, grinding through an 800-mesh sieve, and calcining at 800°C for 8 hours; the mass ratio of the aluminum source, niobium source, scandium source, tellurium source, alcohol solvent and sodium acetate is 1:0.1:0.03:0.003:20:3; the aluminum source is aluminum chloride; the niobium source is niobium nitrate; the scandium source is scandium nitrate; the tellurium source is sodium tellurate; and the alcohol solvent is ethanol.
[0078] A method for preparing the anti-pollution ultrafiltration membrane comprises the following steps:
[0079] Step S1, mixing hydrophilic modified polyethersulfone, coupling agent, Al-Nb-Sc-O-Te and additives to obtain a mixture, adding the mixture into an organic solvent, heating and stirring for 6 hours to prepare a casting solution;
[0080] Step S2, the casting solution prepared in step S1 is placed in a static state for degassing, and then the film is scraped, and then placed in a deionized water coagulation bath at 75°C, and after the film is formed, it is washed with deionized water and dried naturally to obtain a primary film;
[0081] Step S3, polyethylene glycol diacrylate, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt and 1-allyl-3-vinyl imidazole chloride are added into water in sequence, and dispersed evenly to obtain a dispersion; then the primary membrane is immersed in the dispersion, and heated under a nitrogen atmosphere by using 60 The membrane is irradiated by a Co-γ ray source, and then washed and dried to obtain an anti-pollution ultrafiltration membrane.
[0082] The mass ratio of the mixed material and the organic solvent in step S1 is 1:10; the organic solvent is N,N-dimethylacetamide; the temperature of heating and stirring in step S1 is 80°C; the mass ratio of polyethylene glycol diacrylate and water in step S3 is 1:8; the irradiation in step S3 is carried out at room temperature, the irradiation dose rate is 430Gy / min, and the irradiation dose is 70kGy.
[0083] Comparative Example 1
[0084] A pollution-resistant ultrafiltration membrane and a preparation method thereof are basically the same as those in Example 1, except that polyethersulfone is used instead of hydrophilic modified polyethersulfone, and polyethylene glycol diacrylate is used instead of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt.
[0085] Comparative Example 2
[0086] An anti-pollution ultrafiltration membrane and a preparation method thereof are basically the same as those in Example 1, except that 60 nm nano-alumina is used instead of Al-Nb-Sc-O-Te, and polyethylene glycol diacrylate is used instead of 1-allyl-3-vinylimidazole chloride.
[0087] In order to further illustrate the beneficial technical effects of the anti-pollution ultrafiltration membranes involved in each embodiment of the present invention, the anti-pollution ultrafiltration membranes involved in Examples 1-5 and Comparative Examples 1-2 were subjected to relevant performance tests. The test results are shown in Table 1. The test method is as follows: the pure water permeability and retention rate of each product were tested with reference to the detection method of GB / T 32360-2015 "Ultrafiltration Membrane Test Method". The retention rate adopts the bovine serum albumin (BSA) method; the anti-pollution performance is measured by the flux recovery rate. The larger the value of the flux recovery rate, the better the anti-pollution performance. During the test, each anti-pollution ultrafiltration membrane sample was first placed in a cross-flow cell device, and 0.5 g / L bovine serum albumin solution was used as the feed liquid and filtered for 30 minutes; the device was cleaned with deionized water, and then the anti-pollution ultrafiltration membrane sample was inverted in the cross-flow and backwashed at a pressure of 0.02 MPa for 5 minutes; the anti-pollution ultrafiltration membrane sample was reversed, and the pure water permeability after backwashing was measured at 0.1 MPa, and the flux recovery rate was calculated (flux recovery rate = pure water permeability after backwashing / pure water permeability × 100%).
[0088] It can be seen from the data in Table 1 that the anti-pollution ultrafiltration membranes involved in the embodiments of the present invention have higher pure water permeability, better anti-pollution and higher BSA retention rate than the comparative example products; the combined use of hydrophilic modified polyethersulfone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, Al-Nb-Sc-O-Te and 1-allyl-3-vinylimidazolium chloride is beneficial to improving the above properties.
[0089] Table 1
[0090] project Pure water permeability Anti-pollution Retention rate unit <![CDATA[L / (m 2 ·h)]]> % % Example 1 375 99.85 99.4 Example 2 380 99.88 99.6 Example 3 383 99.90 99.7 Example 4 384 99.94 99.7 Example 5 386 99.97 99.9 Comparative Example 1 317 96.13 98.6 Comparative Example 2 349 98.28 98.0
[0091] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. An anti-pollution ultrafiltration membrane, characterized in that: The raw materials are as follows: 80 parts of hydrophilic modified polyethersulfone, 2-4 parts of coupling agent, Al-Nb-Sc-O-Te 3-5 parts, 15-25 parts of additives, 5-8 parts of polyethylene glycol diacrylate, 2-4 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 3-5 parts of 1-allyl-3-vinyl imidazolium chloride; the hydrophilic modified polyether sulfone is trishydroxymethylaminomethanesulfonic acid modified polyether sulfone; the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570; the additive is any one of polyvinyl pyrrolidone K-30, polyvinyl pyrrolidone K-17, polyvinyl pyrrolidone K-60, polyethylene glycol 200, and polyethylene glycol 400; the number average molecular weight of the polyethylene glycol diacrylate is 400; The preparation method of Al-Nb-Sc-O-Te comprises the following steps: dispersing an aluminum source, a niobium source, a scandium source and a tellurium source in an alcohol solvent, stirring evenly, slowly adding sodium acetate, stirring vigorously for 2 hours, transferring the mixture to a hydrothermal reactor lined with polytetrafluoroethylene, and reacting at 190-222° C. for 12-24 hours; After cooling, the mixture is repeatedly washed with anhydrous ethanol, dried in a vacuum drying oven at 80-90°C to constant weight, ground through a 400-800 mesh sieve, and then calcined at 600-800°C for 5-8h; the mass ratio of the aluminum source, niobium source, scandium source, tellurium source, alcohol solvent, and sodium acetate is 1:(0.05-0.1):(0.01-0.03):0.003:(10-20):3; The method for preparing the anti-pollution ultrafiltration membrane comprises the following steps: Step S1, mixing a hydrophilic modified polyethersulfone, a coupling agent, Al-Nb-Sc-O-Te and an additive to obtain a mixture, adding the mixture into an organic solvent, heating and stirring for 4-6 hours, and preparing a casting solution; Step S2, the casting solution prepared in step S1 is placed in a static state for degassing, and then the film is scraped, and then placed in a deionized water coagulation bath at 65-75° C., and after the film is formed, it is washed with deionized water and dried naturally to obtain a primary film; Step S3, polyethylene glycol diacrylate, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt and 1-allyl-3-vinyl imidazole chloride are added to water in sequence, and dispersed evenly to obtain a dispersion; then the primary membrane is immersed in the dispersion and heated under a nitrogen atmosphere by using 60 The membrane is irradiated by a Co-γ ray source, and then washed and dried to obtain an anti-pollution ultrafiltration membrane.
2. The anti-pollution ultrafiltration membrane according to claim 1, characterized in that: The preparation method of the hydrophilic modified polyether sulfone comprises the following steps: adding polyether sulfone, polyphosphoric acid, phosphorus pentoxide and tris(hydroxymethyl)aminomethane sulfonic acid into a reaction kettle equipped with dimethyl sulfoxide and a reflux device, stirring and reacting at 175-183° C. for 6-10 hours, then removing the solvent by rotary evaporation, washing the product with water for 3-6 times, and finally drying it in a vacuum drying oven at 90-100° C. to a constant weight to obtain the hydrophilic modified polyether sulfone.
3. The anti-pollution ultrafiltration membrane according to claim 2, characterized in that: The mass ratio of the polyethersulfone, polyphosphoric acid, phosphorus pentoxide, tris(hydroxymethyl)aminomethanesulfonic acid) and dimethyl sulfoxide is 3:(0.1-0.3):(0.3-0.5):(0.5-1):(10-16); the polyethersulfone is selected from the brand 3000MP polyethersulfone.
4. The anti-pollution ultrafiltration membrane according to claim 1, characterized in that: The aluminum source is at least one of aluminum chloride and aluminum nitrate; the niobium source is at least one of niobium chloride and niobium nitrate; the scandium source is scandium nitrate; the tellurium source is sodium tellurite; and the alcohol solvent is at least one of ethanol, ethylene glycol, and n-butanol.
5. The anti-pollution ultrafiltration membrane according to claim 1, characterized in that: The mass ratio of the mixed material to the organic solvent in step S1 is 1:(6-10); the organic solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; and the heating and stirring temperature in step S1 is 60-80°C.
6. The anti-pollution ultrafiltration membrane according to claim 1, characterized in that: The mass ratio of polyethylene glycol diacrylate to water in step S3 is 1:(5-8); the irradiation in step S3 is carried out at room temperature, the irradiation dose rate is 10-430 Gy / min, and the irradiation dose is 10-70 kGy.
Citation Information
Patent Citations
Preparation method of antifouling ultrafiltration membrane
CN110449036B
Pollution-resistant polyethersulfone ultrafiltration membrane
CN115646223A
Antibacterial and anti-pollution microporous membrane and preparation method thereof
CN117983073A
Cited By
Ultrafiltration membrane for purifying and separating electroplating effluent and preparation method thereof
CN120189825A